Interactions Among Expressed MicroRNAs and mRNAs in the Early Stages of Fowl Adenovirus Aerotype 4-Infected Leghorn Male Hepatocellular Cells - Wu, Ning; Yang, Bo; Wen, Bo; Wang, Ting; Guo, Jiaona; Qi, Xuefeng; Wang, Jingyu (Frontiers in Microbiology, 2020)
Hydropericardium-hepatitis syndrome (HHS) is caused by some strains of fowl adenovirus serotype 4 (FAdV-4). However, the mechanism of FAdV-4 entry are not well understood. Therefore, to investigate the changes in host cellular response at the early stage of FAdV-4 infection, a conjoint analysis of miRNA-seq and mRNA-seq was utilized with leghorn male hepatocellular (LMH) cells at 30 min, 60 min, and 120 min after FAdV-4 infection. In total, we identified 785 differentially expressed (DE) miRNAs and 725 DE mRNAs in FAdV-4-infected LMHs. Most miRNAs and mRNAs, including gga-miR-148a-3p, gga-miR-148a-5p, gga-miR-15c-3p, CRK, SOCS3 and EGR1, have not previously been reported to be associated with FAdV-4 infection. The conjoint analysis of the obtained data identified 856 miRNA-mRNA pairs at the three time points. The interaction network analysis showed that gga-miR-128-2-5p, gga-miR-7475-5p, novel_miR205, and TCF7L1 were located in the core of the network. Furthermore, the relationship between gga-miR-128-2-5p and its target OBSL1 was confirmed using a dual-luciferase reporter system and a real time quantitative polymerase chain reaction (RT-qPCR) assay. In vitro experiments revealed that both gga-miR-128-2-5p overexpression and OBSL1 loss of function inhibited FAdV-4 entry. These results suggested that gga-miR-128-2-5p play an important role in FAdV-4 entry by targeting OBSL1. To the best of our knowledge, the present study is the first to analyze host miRNA and mRNA expression at the early stage of FAdV-4 infection; furthermore, the results of this study help to elucidate the molecular mechanisms of FAdV-4 entry.